Prevalence of bovine immunodeficiency-like virus in bulls as determined by serology and proviral detection. - Jacobs, R M (1998)
We found the rate of bovine immunodeficiency-like virus (BIV) infection among bulls to be 9.6% using serology and 12.6% when tested by the polymerase chain reaction (PCR) for the presence of BIV provirus in peripheral blood leukocytes. Previously, we determined the frequency of BIV infection among the general dairy cow population in Ontario to be 5.5% based on serological analysis. Apparently, serological testing detects only 77% of BIV-infected bulls. Since almost a quarter of BIV-infected bulls may be seronegative, it is recommended that the PCR test be used to identify BIV-infected individuals. It is clear from the data presented here and supported by experimental studies that the latent carrier state is a relatively common outcome in ruminants infected with BIV.